Antioxidant activity and total phenolic content of earthworm paste of Lumbricus rubellus (red worm) and Eudrilus eugenia (African night crawler) - Mohammed Aldarraji, Qasim; Halimoon , Normala; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2013)
Earthworm paste (EP) has many therapeutic properties such as antioxidant, anti-inflammatory, anticancer and antibacterial activities. Antioxidant properties of the earthworm paste extract may attribute to high phenolic compounds. This study involved quantification of phenolic compounds and evaluation of the antioxidant activity of earthworm paste (EP) from Lumbricus rubellus (red worm) and Eudrilus eugeniae (African night crawler). Three types of solvents were used: 75% methanol, 80% methanol and 80% ethanol. Total phenolic compounds were quantified spectrophotometrically using Folin-Ciocalteu reagent. The antioxidant activity of earthworms paste was evaluated using DPPH (1,1-diphenyl-1-2-picrylhydrazl) method. The extraction of phenolics with 80% ethanol in both species yielded the highest amount of phenolics, 220.6 mg/L, in the African night crawler extract and 247.00 mg/L in the red worm extract. Extraction with 80% methanol yielded 217.00 mg/L of phenolics in the African night crawler extract and 228.00 mg/L in the red worm extract. Extraction with 75% methanol yielded higher amounts in red worm (237.00 mg/L) than in African night crawler (207.00 mg/L). EP of the African night crawler yielded a greater amount of phenolic compounds than the red worm. DPPH assay showed that the inhibition activity of African night crawler (95.23%) was significantly higher than that of the red worm extract (38.26%) in 80% methanol, whereas, in 80% ethanol, the inhibition activity of African night crawler (48.13%) was not significantly different from that of the red worm extract (47.73%). Inhibition of antioxidant activity of African night crawler extract in 75% methanol (48.13%) was higher than that of the red worm extract (47.93%). The study showed that earthworm paste has notable amounts of phenolic compounds that have significant antioxidant activity.